Relationship of Traffic Noise with High Blood Pressure to Pedicab Drivers Around Purabaya Bus Station Surabaya - Shita Addina; Soedjajadi Keman (Universitas Airlangga, 2015)
Abstract: The existence of bus station can make some problems, one of which is the traffic noise. Traffic noise can induce an increased blood pressure. Therefore, the purpose of this study was to analyzed the relationship between level of traffic noise and increased blood pressure in pedicab drivers around Purabaya bus station. The study was carried out using by cross sectional method. Measurement of traffic noise was carried out around Purabaya bus station Surabaya with Sound Level Meter. Measurement of blood pressure with sphygmomanometer. Sampling method used by simple random sampling with 22 respondents respectively and then total of respondents are 44 respondents. The result of study indicated there was a relationship between the level traffic noise with increased blood pressure (hypertension) (p = 0.034). Another factor related to blood pressure was descendants of the family history (p = 0.002). It was concluded that traffic noise related with increased blood pressure in pedicab drivers. Suggested for the next researcher doing the measurement noise more than a day to get the actual average noise level. In addition, other factors related to the blood pressure should examined to get main factor of hypertension.Keywords: traffic noise, blood pressure, pedicab drivers